FORENSIC QUALIFICATION OF MECHANICAL TRAUMA IN COMBINATION WITH TETANUS INFECTION IN THE TRAUMATIC INFECTIOUS PROCESS - Voronov, V.T.; Gavrylyuk, A.O.; Moroz, L.V.; Voronova, T.V. (World of Medicine and Biology, 2019)
The role of Cl. tetanus which complicates the traumatic process of mechanical damage to the body is well-known in cases of presence and activation in the wound duct of tetanus infection. Combined bodily injury requires a forensic qualification of the severity of the injury, taking into account the effects of Cl. tetanus. However, the regulations of the forensic medical examination (FM) do not offer experts comprehensive information on the methods of diagnosis of the specific time of entering the spores of tetanus into the body, as well as the beginning of pathogenic manifestation of infection. Therefore, expert findings on the qualification of mechanical trauma, which is burdened with a tetanus disease, often cause controversial debate. In order to solve the problem of FM in the qualification of combined trauma, the methods of retrospective causal system modeling of causal dependence of traumatic-infectious process and method of quasi-formal reproduction of simulated objects. Shown in the model is an example of a traumatic-infectious process, which is the object of Cl. tetanus manifests in the body as a pathogenic pathogen, and thus determines the tetanus disease. However, it is proved that the infectious process is formed at an unpredictable time after the introduction of the spores Cl. tetanus into the body through damaged skin. Thus, it was determined that the forensic qualification of the severity of the combined trauma (mechanical damage to the skin and tetanus infection) could not be specified at a specific time. The results of the causal system analysis allow to improve the informative recommendations of forensic experts regarding the establishment of qualification of the degree of severity of mechanical damage that is combined with tetanus infection.